hæc pictura completa fuit: Om kalkmalerier og rammer - Bolvig, Axel (Hikuin, 2007)
hæc pictura completa fuit On Wall Paintings and Frames By Axel Bolvig The caption or another linguistic statement try to bind the visual messages. So is the situation in modern society (cf. Roland Barthes). But medieval imagery does communicate on its own without a linguistic »ancrage«. It is due to a well-developed iconography. It leads to the question, what is an image? After the development of oil painting, woodcut and other kinds of portable images we can answer, an image is what is within the frame. Dealing with wall paintings we face the problem that most subjects have no frame. In a Romanesque decoration the extension of the wall can be perceived as the frame of several individual subjects. The totally painted background does also serve as a pictorial markation. In a vaulted late medieval church we find paintings all over the church. The white background of the individual subjects does not constitute a framing, on the contrary there is no difference between the white background of depicted subjects and the whitewashed surface of the rest of the church. Consequently the church building constitutes the frame and all the individual subjects are to be perceived as one image. This is in accordance with the understanding of medieval painters. All the survived inscriptions about decorations use the word pictura in the singular form. Even the complete decoration of Bellinge church is defined as one picture. Especially after the invention of photography we are used to a fragmented representation of medieval wall paintings, which in a way is a violation towards medieval perception. But a still more detailed fragmentation is necessary to do research in the paintings. The image database with Danish wall paintings at www.kalkmalerier.dk contains at the time of the writing of this article more than 5.000 pictures and it is a useful tool for research, which could never be done by visits to the churches spread all over the country. And by help of IT we now can make 3D programmes offering a virtual church interior where all the fragmented subjects are combined to one pictura.